Audits and inspections are never enough: a critique to enhance food safety - Powell, Douglas A.; Paterno, Maria Sol Erdozain; Dodd, Charles; Morley, Katija A.; Costa, Roy E.; Chapman, Benjamin J. (My University, 2013)
Internal and external food safety audits are conducted to assess the safety and quality of food including on-farm production, manufacturing practices, sanitation, and hygiene. Some auditors are direct stakeholders that are employed by food establishments to conduct internal audits, while other auditors may represent the interests of a second party purchaser or a third-party auditing agency. Some buyers conduct their own audits or additional testing, while some buyers trust the results of third-party audits or inspections. Third-party auditors, however, use various food safety audit standards and most do not have a vested interest in the products being sold. Audits are conducted under a proprietary standard, while food safety inspections are generally conducted within a legal framework. There have been many foodborne illness outbreaks linked to food processors that have passed third-party audits and inspections, raising questions about the utility of both. Supporters argue third-party audits are a way to ensure food safety in an era of dwindling economic resources. Critics contend that while external audits and inspections can be a valuable tool to help ensure safe food, such activities represent only a snapshot in time. This paper identifies limitations of food safety inspections and audits and provides recommendations for strengthening the system, based on developing a strong food safety culture, including risk-based verification steps, throughout the food safety system.
Keywords: Food safety; Audit; Inspection; Culture